The Influence of Family Support, Lecturer Support, Competency Performance on the Academic Behavior of Gen Z Students - Mahendra, Arka; Callista, Zara (Journal of Current Research In Multidisciplinary, 2024)
The study examined the impact of family support, lecturer support, and competency performance on the academic behavior of Gen Z students. This research used a non-probability sampling technique. The non-probability sampling techniques used are judgmental sampling and snowball sampling. We employed secondary data collection techniques from journals and articles in this study. We used survey research or a distributed questionnaire via Google Forms as the primary data collection technique. This method includes collecting primary data from Generation Z students, totaling 100 respondents for the main test and 30 respondents for the pre-test. The research results revealed that women made up the majority of the 74 respondents (62.2%), with a birth year range of 2003-2006 (98.6%), and all of them resided in Tangerang (100%). The hypothesis results show that family support and lecturer support have no effect on the academic behavior of Gen Z students in Tangerang because the t-count for both is smaller than the t-table and the significance value is above 0.05. On the other hand, competency performance has a significant influence on academic behavior, as evidenced by the t-count of 5.350, which is greater than the t-table, and a significance value below 0.001